Possibilities and limitations of integrating peer instruction into technical creativity education - Wang, Shijuan; Murota, Masao (Instructional science, 2016)
The effects of active peer–peer interaction on the generation of new hypotheses or models and the increase of new solutions have attracted widespread attention. Therefore, the peer discussion portion of peer instruction is supposedly effective in developing students' creativity. However, few empirical research involves how to adapt peer instruction to concrete subject areas to increase different-level students' creativity. This study aimed to assess the possibilities and limitations of peer instruction in teaching technical creativity to different-level students through empirical teachings in authentic high school classrooms. The results showed that peer discussion was effective in improving the creative performances of all (higher-, medium-, and lower-level) students when they have already had original ideas. However, in facilitating lower-level students to generate their own ideas from nothing, peer instruction was not as good as a teacher-centered teaching method—explicit technical creativity teaching. To develop different-level students' creativity, a hybrid-type of peer instruction, i.e., the combination of peer instruction and explicit technical creativity teaching, was suggested.